Research Progress of Reactor Thermal-Hydraulic Characteristics Under Ocean Conditions in China - Jie, Xin (Frontiers in Energy Research, 2020)
Floating nuclear power plants are affected by sea wind and waves, which will produce various forms of movement, and cause changes in the thermal and hydraulic characteristics of the reactor core and threaten the safety of reactor operation. In response to the R&D and design requirements of floating nuclear power plants, the research progress on the thermal-hydraulic characteristics of reactors under ocean conditions in China are reviewed in this paper. The emphasis is put on flow heat transfer, bubble behavior, flow instability, and critical heat flux under ocean conditions. Research progresses as well as the issues that need to be focused on in the future research are discussed in detail.